ARENA OLAHRAGA ELEKTRONIK RAMAH LINGKUNGAN DI KELAPA GADING - Thalia Remita; Suryono Herlambang (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
According to millenials, the usage of internet is a common subject, as internet is also part of their daily life and routines. Together with the existence of internet itself, video games with the basis of using internet called "Electronic Sport" or "E-Sport" has started to born and develop from time to time. In Indonesia, E-Sport has already been recognized as one of the national sport branch, as a result, the demand for E-Sport arena started to rise alongside with the growing amount of E-Sport players in Indonesia.Upon this personal project, the goal is to fulfill the demand of E-Sport arena in Indonesia that is currently lacking. The insufficient amount of E-Sport arena in Indonesia has many potentials to create another complications. For example, in general, E-Sport players prefer to operate their video games at home, therefore, the players are not interacting with each other in real life and starting to become ignorant to the environment around them. Players also tend to develop a careless habit which makes them unable to control the duration of their playing time, hence, it might affect their health condition and career.With the study of typology of arena and using the concept of hybrid architecture, the purpose of E2SA E-Sport arena is being built is to provide E-Sport players a place where they can build connections by interacting with each other in real life. Furthermore, by having a place besides their house, they can control their playtime and health effectively. Finally, E2SA is capable to improve the attribute of Indonesian E-Sport players and produce higher quality players to compete in the international level. AbstrakBagi generasi millennial, penggunaan internet merupakan hal yang umum. Internet merupakan bagian dari kehidupan sehari-hari generasi millennial, dengan keberadaan internet itu sendiri, muncul permainan-permainan berbasis internet yang biasa disebut dengan E-Sport. Electronic Sport atau E-Sports ini khususnya di Indonesia sudah diakui sebagai salah satu cabang olahraga nasional. Perancangan E-Sport Arena dilatar belakangi oleh meningkatnya minat terhadap olahraga E-Sport di Indonesia, proyek ini menjawab problem yang timbul atas permasalahan dan kebutuhan generasi millennial atas olahraga berbasis video game. Problem utama yang ditimbulkan dari permainan E-Sport adalah E-Sport biasanya dimainkan di dalam rumah, sehingga pemain cenderung menjadi tertutup dengan lingkungan sekitar dan menimbulkan kurangnya interaksi dengan orang lain. Pemain juga cenderung kurang beraktivitas dan kurangnya control terhadap waktu sehingga menimbulkan penyakit-penyakit tertentu. E2SA dibangun menggunakan pendekatan metode tipologi arena yang dikembangkan menggunakan kondep arsitektur hybrid untuk menampung minat pemain-pemain E-Sport yang terus berkembang di Indonesia serta mempersiapkan masyarakat Indonesia untuk bertanding di jenjang internasional, dengan menyediakan sarana penunjang bagi pemain agar dapat beristirahat, berolah raga dan membangun koneksi antar pemain E-Sport sehingga pemain dapat diarahkan untuk melakukan kegiatan-kegiatan positif sehingga pemain dapat menjaga kesehatan dan memiliki hubungan sosial yang positif antar pemain sehingga dapat berlatih secara maksimal dan menghasilkan kualitas pemain E-Sport yang berkualitas.